2007
DOI: 10.1007/s00520-007-0243-x
|View full text |Cite
|
Sign up to set email alerts
|

Developing a literature base to understand the caregiving experience of parents of children with cancer: a systematic review of factors related to parental health and well-being

Abstract: Various limitations and gaps in the current literature were identified in our review. Future research to understand the complex interrelationships between factors involved in the caregiving process should examine hypotheses that are guided by a theoretical framework and tested using advanced statistical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
168
2
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(191 citation statements)
references
References 78 publications
(145 reference statements)
8
168
2
13
Order By: Relevance
“…Indeed, some studies suggest that children's behavioral problems may be a prominent source of stress for the parents, compared to the child's disability [35,37]. This present finding provides additional support to Klassen [5] which identified child characteristics as one of the most important variable in their care giving process and caregiver burden model.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Indeed, some studies suggest that children's behavioral problems may be a prominent source of stress for the parents, compared to the child's disability [35,37]. This present finding provides additional support to Klassen [5] which identified child characteristics as one of the most important variable in their care giving process and caregiver burden model.…”
Section: Discussionsupporting
confidence: 77%
“…A study reviewed 29 articles on the psychological effects of childhood cancer on parents concluded that they experienced significantly more distress as opposed to a normative group of parents [4]. They reported to experience poorer physical and psychosocial quality of life [5,6]. The majority of studies suggest that, at some point of time, the parents display a range of emotional challenges especially anxiety and stress symptoms [7] and these two were found to be significantly correlated [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional work with larger samples will be required to clarify the similarities and differences in maternal and paternal responses regarding the QOL of BT children. Although our reliance on exclusively maternal reports may limit the generalizability of our findings, child and adolescent BT patients are usually under maternal care, 1 and mothers are recognized as the main source of emotional support for children with cancer. 24 We therefore believe that the findings reported herein are culturally appropriate for other country.…”
Section: Discussionmentioning
confidence: 93%
“…Difficulties for the patient's parents include fear of relapse, anxiety, the need to assimilate information received, care provided to healthy children, attempts to adapt to the new health condition, provide care in the event of side effects, and care provided for intercurrences, among other situations, which harm the family's quality of life (Beck & Lopes, 2007a, 2007bBjörk, Wiebe, & Hallström, 2005;Clarke, Fletcher, & Schneider, 2005;Eiser & Eiser, 2007;Klassen et al, 2007;McGrath, 2001).…”
mentioning
confidence: 99%